قاعذة العبرة بعموم اللفظ لا بخصوص السبب دراسة نظرية تطبيقية - طبه, عبد الحميم (University of Eloued-جامعة الوادي, 2015)
In the research,I have done a precise study of important original religionist rule that is named « the best way is the general expression and not in the private reason ». I have studied the rule in theory side and in practice side. In the theory side ; I used the general subject and the private one in the original religionist. I have shown the important problems that the original religionist mentioned in this subject. In the generality research ; I dealt for exemple with generality theories and the generality symbols on some individuals and the variation of the religionist on it,and the division of the generality.In the private research I have given for exemples : the difinition of the private and the defferent kinds of privation. I also showed the meaning of the rule by explaining its lexical items and meanings.I also showed the defferent repports presented by the religionist , I mentioned their proof then I wrote the disagreement in this. I have shown the most useful of discussion and I have mentioned the relation between the rule that has been studying and the rule named « problems of hight persons have no generality »,I gave practical exemples over the last rule. But in the practice side of research,I have forced the research with practical solutions that the scientist of religion practiced the rule and I gave the final suggestions basing on it. The practical exemples were in defferent part of religion : first in praying then in family,finally in the limits. At the end ,I ask God that my work will be good and beneficial,and thanks to God of the world.
مذكرة ماستر
Keywords: قاعذة العبرة/اللفظ/السبب; The basis of the lesson / the pronunciation / the reason